Ultrasensitive Chemiresistive Gas Sensors Based on Dual-Mesoporous Zinc Stannate Composites for Room Temperature Rice Quality Monitoring - Jinyong Xu; Xuxiong Fan; Kaichun Xu; Kaidi Wu; Hanlin Liao; Chao Zhang (Nano-Micro Letters)
Highlights Dual-mesoporous heterostructured semiconducting metal oxides were directly fabricated using a simple template-free method, optimizing porosity and improving surface area for enhanced gas-sensing. The fabricated sensor exhibited high sensitivity (11.03 for 13 ppm), a rapid response time (21 s), and an impressively low theoretical detection limit (431 ppb) for 2-Undecanone at room temperature. An innovative real-time method was developed for analyzing characteristic biomarkers of rice aging, enabling accurate and timely monitoring of rice quality.